2001
DOI: 10.1094/mpmi.2001.14.7.867
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Binding Between Resistance Gene Product Cf-9 of Tomato and Avirulence Gene Product AVR9 of Cladosporium fulvum

Abstract: The gene-for-gene model postulates that for every gene determining resistance in the host plant, there is a corresponding gene conditioning avirulence in the pathogen. On the basis of this relationship, products of resistance (R) genes and matching avirulence (Avr) genes are predicted to interact. Here, we report on binding studies between the R gene product Cf-9 of tomato and the Avr gene product AVR9 of the pathogenic fungus Cladosporium fulvum. Because a high-affinity binding site (HABS) for AVR9 is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 41 publications
2
51
0
Order By: Relevance
“…This was higher than expected for the monomeric form of Cf-9:myc, strongly suggesting that Cf-9 is part of a protein complex in the membrane. No cross-reacting band was observed when extracts from untransformed Petit Havana plants were used (data not shown) (Luderer et al, 2001). To further confirm the specificity of the cross-reacting bands in Figure 4A, eluted fractions 23 to 25 from the gel filtration column containing Cf-9:myc were pooled and subjected to immunoprecipitation.…”
mentioning
confidence: 79%
“…This was higher than expected for the monomeric form of Cf-9:myc, strongly suggesting that Cf-9 is part of a protein complex in the membrane. No cross-reacting band was observed when extracts from untransformed Petit Havana plants were used (data not shown) (Luderer et al, 2001). To further confirm the specificity of the cross-reacting bands in Figure 4A, eluted fractions 23 to 25 from the gel filtration column containing Cf-9:myc were pooled and subjected to immunoprecipitation.…”
mentioning
confidence: 79%
“…Furthermore, Luderer et al (2001) demonstrated that COS-7 cells, transfected with the Cf-9 gene, presented the protein on the plasma membrane. We showed that expression of LeEix2 in the COS-7 cells enables the binding of EIX in the absence of other plant proteins and hence indicates direct binding between the EIX and the LeEix2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, interaction between the cytoplasmic receptor Pi-ta and the corresponding AVR-Pita is required to induce resistance response (Jia et al, 2000). While these interactions are crucial for plant defense induction, the Avr9 elicitor exhibits high affinity binding to plasma membranes isolated from both resistant and susceptible tomato (Lycopersicon esculentum) cultivars (Kooman-Gersmann et al, 1996;Luderer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated in several cases that Cf9 does not directly bind Avr9. 21 Despite these facts, it would seem that Cf receptors may undergo endocytosis, given that they possess a YXXφ domain and are capable of having their activity modulated by the endocytic protein EHD2.…”
mentioning
confidence: 99%